As políticas públicas de urbanização e regularização fundiária no processo de inclusão social: o PROAP Rio de Janeiro - Lazo, María Verónica Lazo (2005)
This work objectives to investigate how the public policies of urbanization and land regularization of the Program of Urbanization of Informal Settlements - PROAP, in Rio de Janeiro allow the social inclusion and the rescue of the citizenship of the poor populations. To reach this objective the two programs of PROAP were analyzed into two communities both beneficed by each one of these programs. First, the social exclusion and how it reflects itself in the form of appropriation of the territory and in the type of housing was deeply analyzed. It leads the analysis of the public policies. As a next step, a brief historical analysis was made to include the PROAP in the historical context, and this was analyzed in each one of its stages. Finally, through a qualitative approaching, the slum of Vigário Geral and the irregular settlement of Ana Gonzaga have been researched, both were chose by their singular characteristics and, according to speech of the inhabitants, it was evaluated how the Program contributes in the social inclusion in these communities.